Abstract ID: 36 Geant4 modeling of targeted radionuclide therapy for brain metastasis. (October 2017) - Ackerman, Nicole; Falzone, Nadia; de la Fuente Rosales, Liset; Vallis, Katherine A.; Bernal, Mario
Abstract : Many patients with breast cancer develop brain metastases, which are typically treated through whole-brain irradiation. As a potential alternative treatment, targeted radionuclide therapy (TRT) could be delivered early, targeting the areas of the vasculature where tumor cells are penetrating into the brain. We have developed a Monte Carlo model representing brain vasculature to evaluate and understand a variety of potential therapeutic nuclides: (alpha emitters) Pb-212, At-211, Ac-225, Bi-213, and Tb-149; (beta/Auger electron emitters) Lu-177, Tb-161, I-124, In-111, Y-90, Zr-89, and Ga-67. The micron-scale dose distributions from all radioactive decay products were modeled in Geant4, as well as eV-scale interactions through the G4DNA models[1] . These interactions were then superimposed on an atomic-scale DNA model[2] to estimate strand break yields. Some of the alpha emitters have decay chains with multiple daughter nuclei; we investigate the change in dose profiles and biological effectiveness as a function of time. Alpha emitters have higher doses per decay, and the depth-dose profiles fall off less quickly. The general qualities of the depth-dose profiles are maintained through biologically-relevant variations in vasculature geometry.